Application of Polymer Inclusion Membranes Doped with Alkylimidazole to Separation of Silver and Zinc Ions from Model Solutions and after Battery Leaching - Radzyminska-Lenarcik, Elzbieta (Materials (Basel), 2020)
New materials, such as polymer inclusion membranes, can be used for water and wastewater treatment. In this paper, the selective transport of silver(I) and zinc(II) ions from nitrate solutions through the polymer inclusion membranes (PIMs), which consist of cellulose triacetate as a polymeric support, o-nitrophenyl pentyl ether as a plasticizer, and either 1-hexylimidazole (1) or 1-hexyl-2-methylimidazole (2) as an ion carrier, is studied. Both Zn(II) and Ag(I) model solutions (C(M) = 0.001 M, pH = 6.5), as well as the solutions after the leaching of a spent battery with a silver–zinc cell (silver-oxide battery), are tested. The results show that Zn(II) ions are effectively transported through PIMs containing either carrier, whereas Ag(I) is more easily transported through PIMs doped with (1). In the case of the leaching solution after 24 h transport, the recovery coefficients of Ag(I) and Zn(II) for PIMs doped with (1) are 86% and 90%, respectively, and for PIMs doped with (2), 47% and 94%, respectively. The influence of basicity and structure of carrier molecules on transport kinetics is discussed as well. PIMs are characterized by using an atomic force microscopy (AFM) technique.